ln (ln e^e)

I don't remember how to change it, and all I know is that the answer is 1. If anyone can help, it will be very useful. :3

Printable View

- Jul 4th 2010, 01:43 PMorkdorkHelp with Natural Logs
ln (ln e^e)

I don't remember how to change it, and all I know is that the answer is 1. If anyone can help, it will be very useful. :3 - Jul 4th 2010, 01:57 PMpickslides
$\displaystyle \ln (\ln e^e)$

$\displaystyle =\ln (e\ln e)$

$\displaystyle =\ln (e\times 1)$

$\displaystyle =\ln (e)$

$\displaystyle =1$ - Jul 4th 2010, 01:58 PMAlso sprach Zarathustra
$\displaystyle ln (ln e^e)=?$

First the inside expression: $\displaystyle (ln e^e)=elne=e\cdot 1=e$

Now, $\displaystyle ln(ln e^e)=ln e=1$